The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1084/jem.170.4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the molecular target for the suppression of contact hypersensitivity by ultraviolet radiation.

Abstract: This study was conducted to explore the involvement of DNA damage in the suppression of contact hypersensitivity (CHS) by UV irradiation. The opossum, Monodelphis domestica, was used because cells of these marsupials have an enzyme that is activated by visible light (photoreactivating enzyme) and repairs ultraviolet radiation (UVR)-induced pyrimidine dimers in DNA. A single dose of 1,500 J/m2 of UVB (280-320 nm) radiation, representing 2 minimal erythema doses, was administered to the dorsal skin of opossums. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
2
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(132 citation statements)
references
References 40 publications
5
124
2
1
Order By: Relevance
“…UV-induced DNA damage is the major molecular trigger for photoimmunosuppression because reduction of DNA damage is associated with a mitigation of the compromise to the immune system by UV exposure (9,27). In addition, it was recently shown that the well-known antagonism of UV-induced immunosuppression by IL-12 is at least partially due to its capacity to reduce UV-mediated DNA damage (21).…”
Section: Il-18 Prevents Uv-induced Suppression Of the Induction Of Chsmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-induced DNA damage is the major molecular trigger for photoimmunosuppression because reduction of DNA damage is associated with a mitigation of the compromise to the immune system by UV exposure (9,27). In addition, it was recently shown that the well-known antagonism of UV-induced immunosuppression by IL-12 is at least partially due to its capacity to reduce UV-mediated DNA damage (21).…”
Section: Il-18 Prevents Uv-induced Suppression Of the Induction Of Chsmentioning
confidence: 99%
“…This result indicates that IL-12 and IL-18 only share the same effect on preventing UV-induced immunosuppression, whereas IL-18, in contrast to IL-12, is not able to break established tolerance. Because UV-induced immunosuppression can be prevented by reducing DNA damage (9,27), it is obvious that IL-18 like IL-12 appears to prevent immunosuppression via its effect on DNA repair.…”
Section: Il-18 Prevents Uv-induced Suppression Of the Induction Of Chsmentioning
confidence: 99%
“…UV-induced DNA damage, predominantly in the form of cyclobutane pyrimidine dimers (CPDs) or thymine dimers, has been recognized as an important molecular trigger for the suppression of immune responses (Applegate et al, 1989) and initiation of UV-carcinogenesis (Applegate et al, 1989;Kripke et al, 1992;Yarosh et al, 1992). In turn, accelerated or enhanced removal of UV-induced CPDs through the topical application of the bacterial DNA repair enzyme, T4 endonuclease V, impaired the development of skin tumors in mice exposed to chronic UV radiation .…”
Section: Il-12 Prevents Uv-induced Immunosuppression Through Dna Repamentioning
confidence: 99%
“…Studies by Kripke's team were the first to suggest that DNA (and most likely, the pyrimidine dimer) may be the chromophore for UVB-induced immunosuppression (Applegate et al, 1989), and evidence linking DNA damage with immune modulation has come from studies on XP patients (Suzuki et al, 2001). Trans-UCA is a natural component of the strateum corneum, and UV induces a photoisomeric isomerization of trans-UCA to cis-UCA, which appears to be an initiator of the UV-immunosuppression, although its mechanism of action is still uncertain (Halliday & Rana, 2008;Norval et al, 2008).…”
Section: Immune Response and Photoadaptationmentioning
confidence: 99%
“…In the former, the antigen is applied directly to the irradiated body site soon after UV exposure. In the latter, following UV exposure of one part of the body, the antigen is applied to a distant, non-irradiated body site (Applegate et al, 1989).…”
Section: Immune Response and Photoadaptationmentioning
confidence: 99%